Impact of intellectual capital on firm performance: Evidence from South African JSE listed firms - Maluleke, Makungu Juanita (Department of Finance and Tax, 2021)
The new knowledge economy has created a global interest on the valuation of intellectual capital as well as its impact on firm performance and value. Developing economies have relatively only begun to investigate this relationship and progress has already been made in South Africa by a few researchers. The purpose of this study is to add to this investigation by exploring the relationship between intellectual capital and firm performance for South African listed firms in intellectual capital-intensive industries. A gap exists in South African research regarding the long-term impact of intellectual capital on firm performance. This relationship is important to define as firms may well make inappropriate decisions based on short-term relationships that do not create long-term value. This study applies a lag model in an aim to investigate this relationship in addition to the short-term relationship that exists between intellectual capital and firm performance. The study involves a quantitative analysis of data collected from firms in intellectual capital-intensive industries and makes use of the VAIC model developed by Ante Pulic to value intellectual capital. Measures of firm performance used are return on assets, total asset turnover and market capitalization. This study also makes use of panel data covering 62 JSE listed companies over 10 years. Empirical results show mixed outcomes regarding the relationship between intellectual capital and firm performance for both short-term models and lagged models. In some instances, no association was observed between intellectual capital and performance.